Augmentin Induced Exfoliative Dermatitis: Case Report - Karn, Ashish; Shah, Juie; Shah, Rutuva; Patel, Riki; Modi, Bhavya (Journal of Pharmacy Practice and Community Medicine)
Exfoliative dermatitis is a very rare form of drug induced hypersensitivity reaction which usually involves skin and mucous membrane, can be seen from a few days to several weeks after the administration of drug.1 Amoxicillin is a broad spectrum antibiotic, belongs to class amino-penicillin of beta-lactum antibiotics, and it is generally active against gram-positive bacteria, gram-negative bacteria and anaerobes which represent the major species present in the stomach, biliary tract and colorectum. Therefore, it is a preferred choice as a prophylaxis for abdominal surgery. It is usually combined with clavulanic acid which is a beta-lactamase inhibitor, in order to maintain greater efficacy and activity against beta-lactamase-positive strains.2 Here is a case of delayed type of hypersensitivity reaction of a 58 years old female who developed multiple erythematous scaly plaques with erosion sign and exfoliation of skin seen all over the four limbs following the administration of Augmentin.
Keywords: Augmentin; Erythoderma; Exfoliative Dermatitis; Delayed Hypersensitivity; Aminopenicillin; Severe cutaneous reaction